THE ROLE OF COREGRAPHIC PREPARATION IN THE EDUCATION OF PSYCHOMOTRIC SKILLS IN CHILDREN WITH THE CIRCULATION BETWEEN 15-17 YEARS - Salup Mărioara (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
Musical accompaniment is a component part of the concept of musical education, and any departure from concordance of movementmusic entails minimizing the effectiveness of performing the proposed motor content. Selection of operational models and their application in the conditions of musical accompaniment in the sense of rhythmic education and motoric musicality contribute to the efficiency of the instructive process and implicitly to the optimization of the dance lesson within the specialized circles.